Micronucleus test and observation of nuclear alterations in erythrocytes of Nile tilapia exposed to waters affected by refinery effluent - Souza, T. D.; Fontanetti, C. S. (Elsevier B.V., 2006)
Micronuclei and nuclear alterations tests were performed on erythrocytes of Oreochromis niloticus (Perciformes, Cichlidae) in order to evaluate the water quality from Paraiba do Sul river, in an area affected by effluents from an oil shale processing plant, located in the city of Sao Jose dos Campos, Brazil-SP. Water samples were collected on 2004 May and August (dry season) and on 2004 November and 2005 January (rain season), in three distinct sites, comprising 12 samples. It was possible to detect substances of clastogenic and/or aneugenic potential, as well as cytotoxic substances, chiefly at the point corresponding to the drainage of oil shale plant wastes along the river. The highest incidence of micronuclei and nuclear alterations was detected during May and August, whereas the results obtained in November and January were insignificant. This work shows that the effluent treatment provided by the oil shale plant was not fully efficient to minimize the effect of cytotoxic and mutagenic substances in the test organism surveyed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: micronuclei test; Oreochromis niloticus; mutagenicity; biomonitoring; oil